THE INFLUENCE OF STORYTELLING METHODS ON EARLY CHILDHOOD ENVIRONMENTALLY CONCERNED CHARACTER THROUGH THE HABIT OF DISPOSING OF GARBAGE IN ITS PLACE - Siti Khomsah Apsari; Aries Dirgayunita (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2026)
This study aims to analyze the influence of storytelling methods on the formation of environmental care character in early childhood, especially through the habit of disposing of garbage in its place at RA Al-Azhar Pondok Wuluh Leces, Probolinggo Regency. The type of research used is a quasi-experimental with a One Group Pretest-Posttest Design . The research subjects consisted of 20 children aged 5–6 years in group B. Data were obtained through an observation sheet of environmental care behavior that includes five main indicators and analyzed using a paired sample t-test with the help of the SPSS program version 25.0. The results showed a significant increase in children's environmental care behavior after the storytelling method was implemented. The average observation value increased from 1.48 in the pretest to 2.44 in the posttest with a significance value of 0.000 <0.05. The highest increase was in the indicator of disposing of garbage in its place and reprimanding friends who litter. These findings indicate that the storytelling method is effective in internalizing environmental care values through a fun, contextual, and appropriate approach to the world of early childhood. Thus, the storytelling method can be used as an alternative character learning strategy in PAUD institutions to foster children's awareness and responsibility for environmental cleanliness